27-u=172

Simple and best practice solution for 27-u=172 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 27-u=172 equation:


Simplifying
27 + -1u = 172

Solving
27 + -1u = 172

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-27' to each side of the equation.
27 + -27 + -1u = 172 + -27

Combine like terms: 27 + -27 = 0
0 + -1u = 172 + -27
-1u = 172 + -27

Combine like terms: 172 + -27 = 145
-1u = 145

Divide each side by '-1'.
u = -145

Simplifying
u = -145

See similar equations:

| 6-2n=4n+4 | | (5x^2-11x+4)= | | x^2+545x-7500=0 | | -3(2-5m)=2(7m-5) | | 6-x=4x+21 | | -7=7.37802(x)+(-4.9)(x^2) | | 5t-2=34-t | | 125+10x=230+2x | | (2q-3)q=27 | | 12y+6=12y+7 | | 5x+28=x | | 42+3x(6+1)+4=24 | | 9x+30=27 | | 20-4(p+1.25)=5+p | | 0=-16x^2+16x+320 | | (2w+7)w=99 | | 0.3a+.7=.5a-.1 | | -8(3p+2)+2(-5+7p)=-66 | | 2(x-1)+3x=3(-2+x) | | 1.5*1= | | (2x^2+8x+1)= | | f(x)=15x+10 | | (2w+11)w=63 | | (8-z)(5z-9)=0 | | 5(1-8k)+4(3k+7)=61 | | 2w+11=63 | | -3-2x+5=5+x-2x | | 8+8(-2g+4)=4(-4g+10) | | 7-5(-7b-1)=-8(3-4b) | | 5+x(53)+8=52 | | -3x^2-6x-21=0 | | 13x+3=23+3x |

Equations solver categories